2019
DOI: 10.1073/pnas.1908977116
|View full text |Cite
|
Sign up to set email alerts
|

PPARα-targeted mitochondrial bioenergetics mediate repair of intestinal barriers at the host–microbe intersection during SIV infection

Abstract: Chronic gut inflammatory diseases are associated with disruption of intestinal epithelial barriers and impaired mucosal immunity. HIV-1 (HIV) causes depletion of mucosal CD4+ T cells early in infection and disruption of gut epithelium, resulting in chronic inflammation and immunodeficiency. Although antiretroviral therapy (ART) is effective in suppressing viral replication, it is incapable of restoring the “leaky gut,” which poses an impediment for HIV cure efforts. Strategies are needed for rapid repair of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 59 publications
3
46
0
Order By: Relevance
“…Understanding these networks might help identify post-biotic therapeutic targets such as PPARα. Beneficial intestinal microbes such as Lactobacillus plantarum activate PPARα, leading to improved intestinal barrier function 6 . Similar beneficial gut microbes have been shown to improve metabolic status in obesity and DM 40 , which may also involve PPARα signaling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Understanding these networks might help identify post-biotic therapeutic targets such as PPARα. Beneficial intestinal microbes such as Lactobacillus plantarum activate PPARα, leading to improved intestinal barrier function 6 . Similar beneficial gut microbes have been shown to improve metabolic status in obesity and DM 40 , which may also involve PPARα signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that hyperglycemia contributes to intestinal barrier disruption, leading to an influx of microbial pathogens and products that exacerbate inflammation 34 . We previously reported that PPARα activation by beneficial microbes may restore intestinal barrier function during chronic inflammation in rhesus macaques by rescuing mitochondrial function 6 . Combined with the in vivo findings in canine DM and in vitro findings on human epithelial cell cultures, our results point to PPARα agonists as a potential therapeutic target in the prevention and amelioration of intestinal barrier dysfunction and mucosal inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other sources of intestinal ROS are mitochondria, particularly electron transport chain and NO synthases (NOS) [ 126 ]. It has been demonstrated that mitochondria have a prominent role in the modulation of gut functions as intestinal barrier protection, mucosal immune response [ 130 , 131 ], and maintenance of an eubiotic intestinal microbiota. A crosstalk between the gut microbiota and mitochondria during exercise is known in the literature.…”
Section: Oxidative Stress In Gastrointestinal Diseasementioning
confidence: 99%